Dual-Signal Readout Nanospheres for Rapid Point-of-Care Detection of Ebola Virus Glycoprotein - Hu, Jiao; Jiang, Yong-Zhong; Wu, Ling-Ling; Wu, Zhen; Bi, Yuhai; Wong, Gary; Qiu, Xiangguo; Chen, Jianjun; Pang, Dai-Wen; Zhang, Zhi-Ling (Analytical chemistry (Washington), 2017)
Rapid detection of highly contagious pathogens is the key to increasing the probability of survival and reducing infection rates. We developed a sensitive and quantitative lateral flow assay for detection of Ebola virus (EBOV) glycoprotein with a novel multifunctional nanosphere (RNs@Au) as a reporter. Each RNs@Au contains hundreds of quantum dots and dozens of Au nanoparticles and can achieve enhanced dual-signal readout (fluorescence signal for quantitative detection and colorimetric signal for visual detection). Antibody (Ab) and streptavidin (SA) were simultaneously modified onto the RNs@Au to label the target and act as signal enhancer. After the target was labeled by the Ab–RNs@Au–SA and captured on the test line, biotin-modified RNs@Au was used to amplify the dual signal by the reaction of SA with biotin. The assay enables naked-eye detection of 2 ng/mL glycoprotein within 20 min, and the quantitative detection limit is 0.18 ng/mL. Additionally, the assay has been successfully tested in field work for detecting EBOV in spiked urine, plasma, and tap water samples and is thus a promising candidate for early diagnosis of suspect infections in EBOV-stricken areas.